Mahatma Gandhi in Cinema - Kaushik, Narendra (Cambridge Scholars Publisher, 2020)
This book analyses 100 years of Hindi cinema, India's principal film industry, to explore how much space it has given to Mahatma Gandhi, the most prominent leader of the Indian struggle for freedom, and his principles.It compares films on Gandhi with the written literature on him, and juxtaposes the celluloid Gandhi with the man who walked on the earth 'ever in flesh and blood'. From his childhood through his legal practice in South Africa to his non-violent struggle against the British Empire in India, the book covers all major events of his life and their portrayal on the silver screen.